Decreased Oleic Acid and Marine n − 3 Polyunsaturated Fatty Acids in Tunisian Patients with Urothelial Bladder Cancer. (3rd October 2018) - Ben Fradj, Mohamed Kacem; Ouanes, Yassine; Hadj-Taieb, Sameh; Sallemi, Ahmed; Kallel, Amani; Jemaa, Riadh; Kaabachi, Naziha; Nouira, Yassine; Feki, Moncef
Abstract: Fatty acids (FAs) are thought to impact carcinogenesis by affecting cell signaling. A case-control study including 250 patients with urothelial bladder cancer (UBC) and 250 controls was conducted. Plasma FAs composition was assessed using capillary gas chromatography. Associations of individual and classes of FAs with UBC were controlled for the main risk factors for UBC. Plasma FAs profile was different in patients compared to controls. Higher levels (third tertile vs. first tertile) in palmitic acid (PA) [multi-adjusted OR (95% CI), 1.83 (1.14–2.92)], and n  − 6: n  − 3 FA ratio [4.13 (2.38–7.16)] were associated with increased risk for UBC [multi-adjusted OR (95% CI), 1.83 (1.14–2.92)]. In contrast, higher levels (third tertile vs. first tertile) in oleic [0.54 (0.34–0.86)], dihomo-γ-linolenic (DGLA) [0.47 (0.29–0.74)], eicosapentaenoic (EPA) [0.32 (0.19–0.52)], and docosahexaenoic (DHA) acids [0.33 (0.20–0.53)] were associated with lower risk for UBC. Although the study design does not allow proving causality, the findings suggest a possible protective role of oleic acid and marine n  − 3 polyunsaturated FAs (PUFAs) against bladder carcinogenesis.